Grain Bending at Deformation of the Steel and Arrangement of Internal Stresses; Advanced Materials Research; Vol. 1085 : Prospects of Fundamental Sciences Development (PFSD-2014) - Gibert I.; Kiseleva S.; Popova N.; Koneva N.; Kozlov E. (Structure Materials, Mechanics and Dynamics of Materials, 2015)
Title screen